Chemical catalyst manipulating cancer epigenome and transcription - Yuki Yamanashi; Shinpei Takamaru; Atsushi Okabe; Satoshi Kaito; Yuto Azumaya; Yugo R. Kamimura; Kenzo Yamatsugu; Tomoya Kujirai; Hitoshi Kurumizaka; Atsushi Iwama; Atsushi Kaneda; Shigehiro A. Kawashima; et al. (Nature Communications)
Abstract The number and variety of identified histone post-translational modifications (PTMs) are continually increasing. However, the specific consequences of each histone PTM remain largely unclear, primarily due to the lack of methods for selectively and rapidly introducing a desired histone PTM in living cells without genetic engineering. Here, we report the development of a cell-permeable histone acetylation catalyst, BAHA-LANA-PEG-CPP44, which selectively enters leukemia cells, binds to chromatin, and acetylates H2BK120 of endogenous histones in a short reaction time. Time-course analyses of this in-cell catalytic reaction revealed that H2BK120 acetylation attenuates the chromatin binding of negative elongation factor E (NELFE), an onco-transcription factor. This H2BK120 acetylation-mediated removal of NELFE from chromatin reshapes transcription, slows leukemia cell viability, and reduces their tumorigenic potential in mice. Therefore, this histone acetylation catalyst provides a unique tool for elucidating the time-resolved consequences of histone PTMs and may offer a modality for cancer chemotherapy.